Impact Of Adoption Of New Feeding Technology On Milk Production By The Farmer Interest Groups Of Vellore District Of Tamil Nadu - Baskaran, D.; Kumar, B. Rajesh; Pandian , A.Serma Saravana (Indian Journal of Veterinary Sciences and Biotechnology, 2011)
A study was carried out on technology diffusion of dairy cattle feed computation for farmer interest groups (FIGs) with locally available feed ingredients in Vellore district. The study was conducted among the 156 farmer interest groups belonging to 12 villages one from each of the 12 blocks of Vellore district. The economics of milk production per litre of milk was calculated for old and new technology. New technology refers to feeding of dairy animals with balanced ration prepared based on the nutrient content of the locally available feed ingredients and old technology refers to the usual non-scientific unbalanced traditional feeding practice. The results revealed that the cost of milk production per litre was Rs.10.22/- for usual technology whereas it was Rs.7.61/- for new feeding technology. The effect of training program on milk production due to adoption of new feeding technology was carried out by paired ‘t’ test. The results clearly indicated that there was 14.20% increase in milk production in new technology compared to the unbalanced ration. There was statistically a significant difference (P
Keywords: Milk production; Balanced ration; Impact